Epidemiology of gonococcal and chlamydial infections in Harrow and Brent. Issue 5 (October 1996) - Matondo, P; Wall, R; Morgan, K; Hickman, M; Dore, C; Kapembwa, M
Abstract : OBJECTIVE: To describe the epidemiology and associated clinical features of gonorrhoea and chlamydial infection and to develop a profile of sexually transmitted diseases (STDs) in an outer London health district. DESIGN: Hospital-based retrospective study. SETTING: Genitourinary medicine clinic, Northwick Park Hospital, Harrow and Brent Health Authority. SUBJECTS: 70 male and female individuals with gonorrhoea and 129 with chlamydial infection, diagnosed consecutively over 28 months in 1992-94. RESULTS: More men than women had gonorrhoea (43 versus 27) but more women than men had chlamydial infection (84 versus 45), p < 0.001. There was a clear tendency for cases with either infection to locate along major road and rail transport routes. Foci of gonococcal infection were concentrated mainly in the densely populated areas, whereas chlamydial cases were more evenly spread. There was no significant effect of gender or type of STD on the odds ratio for residence in Harrow, single marital status or attendance for test of cure. However, the odds ratios for women having sexual intercourse with a regular partner only or previous STD were 5 (95% CI 2.4 to 10.2), p < 0.001 and 0.3 (95% CI 0.18 to 0.69), p = 0.002 times the odds for men, respectively. The odds ratios for patients with gonococcal infection being employed or having sex with a regular partner only were 0.5 (95% CI 0.27 to 0.98), p = 0.04 and 0.30 (95% CI 0.15 to 0.60), p < 0.001 times the odds for patients with chlamydial infection, respectively. Of the women with gonorrhoea and previous pregnancy, 68% gave a history of abortion compared with 44% of those with chlamydial infection (p = 0.03). CONCLUSION: The identification of foci gonococcal and chlamydial infection and apparent location of these infections along the major transport routes in our health district require further study. That chlamydial infection, unlike gonorrhoea, is evenly distributed irrespective of population concentration and deprivation, suggests urgent need for a comprehensive local effort to control both STDs.